RISK FACTORS OF INFERTILITY IN COUPLE OF AGE AGE IN HOSPITALS STELLA MARIS MEDAN YEAR 2018 - Tambun, Mastaida; Simanjuntak, Erledis; Tarigan, Frida Lina (Sari Mutiara Indonesia University Press, 2018)
Infertility is a situation where a woman is not experiencing a pregnancy after marrying within 1 years or more though it has sexual intercourse as much as 2-3 times a week. This research aims to analyze the risk factors for the occurrence of infertility on couples of fertile age research is using design case control. The location of the research conducted in the Stella Maris Hospital 2018. The population in this research is the whole fertile couples who visit during the period April-August 2018, that as many as 150 people. The amount of sample (Case and control) taken comparable 1:1, 40 cases: 40 controls, so that the overall number of samples is 80 samples. Data collection research done using primary data obtained by dividing the questionnaire to respondents, secondary data obtained from records or reports from the Stella Maris Hospital. Data processing is started from the editing, coding, entry, the tabulating. Data analysis using the chisquare test with bivariate and multivariate with logistic regression test. The research results show that there is a relationship age (p = 0.000; OR = 6.6), menstruation cycle (p = 0.005; or = 4.7), companion disease (p = 0,011; OR = 4.6), stress (p = 0.012; OR = 5.9), impaired sperm function (p = 0.002; OR = 8.2). The most dominant variable effect on the incidence of infertility is a malfunctioning of the sperm (p = 0.006; OR = 6.9 95% 1,780-31,313). There for thus to fertile couples Stella Maris Hospital suggestion, to further improve the attention and understanding early on about the risk factors associated with the incidence of infertility interfetilitas genesis so that it can be more minimized